2020
DOI: 10.1088/1757-899x/991/1/012060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vacuum Concentration on Color, Polyphenol and Flavonoid Contents and Antioxidant Activity of Pomelo Citrus maxima (Burm. f.) Merr. Juice

Abstract: Pomelo (Citrus maxima (Burm. f.) Merr). juice is known as an enriched source of antioxidants and nutrients. It is therefore necessary to develop a preservation method for freshly prepared juice. This study aims to determine the effect of the vacuum concentration process on the change in color, bioactive compounds and antioxidant activity of pomelo juice. High pressure showed negligible effects on color. However, longer heating time seemed to cause browning in juice. In comparison with the fresh sample, total c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The L* a* b* color space was used for determination of the color. Further, the total color difference (TCD) of the samples before (control) and after processing and storage were calculated as (Equation ( 3)) [24]:…”
Section: Color Analysismentioning
confidence: 99%
“…The L* a* b* color space was used for determination of the color. Further, the total color difference (TCD) of the samples before (control) and after processing and storage were calculated as (Equation ( 3)) [24]:…”
Section: Color Analysismentioning
confidence: 99%
“…The enormous number of functional, dietary, and biological benefits of pomelo (Citrus grandis or Citrus maxima) are well known in many nations [1][2][3]. Since they have been scientifically shown to have medicinal potential and are safe for humans, many components of this plant, including the leaves, pulp, and peel, have been utilized in traditional medicine for decades.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, fruit TSSC is detected via using a refractometer on extracted juice, which is inefficient, wasteful, and ill-suited for large scale grading [6]. Zhang et al found that the edibility of a pomelo could be nondestructively detected using X-rays [7]; however, the X-ray signal was largely unrelated to the TSSC.…”
Section: Introductionmentioning
confidence: 99%